Decadal and epochal variation of frequency and duration of monsoon disturbances and their secular relationship with rainfall over India (MAUSAM, 2004)
Decadal and epochal variation of frequency and duration of monsoon disturbances like low pressure areas (lows), depressions and Cyclonic Storms (CS) over Indian region are studied by using 110 years (1890-1999) data. No linearly decreasing/increasing trend is observed during 110 years period in any of their frequencies. However, epochal linearly decreasing/increasing trends are noticed in decadal frequencies or duration of different monsoon disturbances. Decadal frequencies of depressions, CS and depressions are decreasing from 1970-79, till recently ended decade of 1990-99. During recent decade, less than half of the total number of depressions and CS are formed compared with 1970-79. On the other hand, total number of lows are increasing significantly from 1960-69 to recent decade, when more than double the number of lows of 1960-69 are formed. Since Indian Summer Monsoon Rainfall (ISMR) also shows interdecadal variation of below normal and above normal phases, variation of frequencies of different monsoon disturbances and their total durations are also examined in similar time scale to understand their relationship with interdecadal variation of ISMR. Stability and secular nature of these relationships are also examined based on their decadal and 10-year moving Correlation Coefficients (CC) for the period 1890-1999. Relationship of decadal anomaly of their frequencies with interdecadal variation of ISMR shows that number of depressions and CS, are higher than the normal during the above normal ISMR decades and less during the below normal decades of ISMR. Reverse is true for the number of lows. The decadal and 10-years moving CC between ISMR and frequencies of different monsoon disturbances and total monsoon disturbance days clearly show epochal variation of their relationship in interdecadal time scale with ISMR. Hence present study shows that secular variation of CC not only exists between ISMR and its various regional and global parameters used in long range forecast of ISMR but also between ISMR and its main synoptic features e.g., monsoon disturbances.